2014
DOI: 10.1111/boc.201400024
|View full text |Cite
|
Sign up to set email alerts
|

Cell death, cavitation and spontaneous multi‐differentiation of dental pulp stem cells‐derived spheroids in vitro: A journey to survival and organogenesis

Abstract: DPSC-derived spheroids can mimic the developmental process of cell survival, cavitation and spontaneous multi-differentiation on matrigel under certain conditions. This work allows for functional studies to investigate organ regeneration with human DPSCs in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…Enhanced expression of Oct 4 and Nanog in sphe roids of human dental pulp stem cells compared to monolayer culture has been revealed with PCR (Xiao et al, 2014). Cells in spheroids obtained from human placenta MSCs underwent epigenetic changes that facilitated increased expression of the pluripotent genes Oct 4, Nanog, and Sox 2 (Guo et al, 2014).…”
Section: Surface Marker Expression In Fetmsc and Fetmsc And Their Sphmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced expression of Oct 4 and Nanog in sphe roids of human dental pulp stem cells compared to monolayer culture has been revealed with PCR (Xiao et al, 2014). Cells in spheroids obtained from human placenta MSCs underwent epigenetic changes that facilitated increased expression of the pluripotent genes Oct 4, Nanog, and Sox 2 (Guo et al, 2014).…”
Section: Surface Marker Expression In Fetmsc and Fetmsc And Their Sphmentioning
confidence: 99%
“…It has been demonstrated that MSC spheroids exhibit increased anti inflammation effect, increased differentiation potential, and enhanced expression of cytokines and pluripotent genes. It facilitates the understanding of organogenesis mechanisms and their application in the regenerative medicine (Alimperti et al, 2014;Bogdanova Jatniece et al, 2014;Guo et al, 2014;Murphy et al, 2014;Xiao et al, 2014;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Spheroid models have been developed for in vitro studies in developmental science and stem cell research (Xiao & Tsutsui 2013, Xiao et al 2014. Also in vitro biocompatibility and toxicity assays have been established based on these culture models (Banerjee & Bhonde 2006.…”
Section: Introductionmentioning
confidence: 99%
“…found that dermal papilla (DP) spheroids of larger size displayed slightly decreased viability on D5 55 . A large spheroid core is often deficient in oxygen and/or nutrients and shows excessive accumulation of catabolites and low pH 56, 57 . We found that CECs in spheroid culture displayed enhanced expression of the corneal endothelial marker ATP1A1.…”
Section: Discussionmentioning
confidence: 99%